Ictal hand signs: Minimal previous attention to these diagnostic indicators Iktale Handsymptome: als diagnostisches Zeichen vernachlässigt - Stefan, Hermann; Strzelczyk, Adam; Schmitt, Friedhelm C. (Clinical Epileptology, 2023)
Ictal hand signs manifest as dystonic, tonic, or non-convulsive rhythmic elementary motor patterns, as well as finger snapping or automatic movement patterns (e.g. fumbling), and psychogenic movements have been reported in a small number of patients. This study demonstrates the various ictal hand signs and discusses the data on lateralization and localization as reported in the literature. In addition to published reports, our case studies are presented.
CRIS-Team Scopus Importer:2023-12-22
Keywords: Automatism; Dystonia; Lateralization; Limb; Localization; Semiology; Tonic posture